JKP Concept in Minister of Labor Regulations Number 4 of 2022 in ILO Perspective and Justice in Law - Deni Setiyawan; Noor Rahmad (Amnesti Jurnal Hukum, 2022)
Minister of Labor Regulations Number 4 of 2022 on the Procedure and Terms of Payment of Old-Age Security Benefits. The purpose of this study is to get an answer from the concept of JKP in Minister of Labor Regulations No. 4 of 2022 on the Procedure and Terms of Payment of Old-Age Security Benefits. This study is included in legal research to find answers to the rules of JKP is in accordance with the convention of the International Labour Organization (ILO) number 102 of 1952 minimum standards of Social Security, the basis for the inclusion of JKP program in order to provide a sense of justice and fulfillment of Social Security for workers. This research uses normative juridical method with case Statute Approach and conceptual approach. The source of research data is in the form of primary legal materials related to the discussion, secondary legal materials are all publications on law that are not official documents and tertiary legal materials are non-legal materials derived from dictionaries, exopedia and magazines. In this case, the JKP rules should be in accordance with the general principles of good governance (AUPB) as mandated in Article 10 of Law No. 30 of 2014 concerning government administration, namely legal certainty, expediency, impartiality, accuracy, not abusing authority, openness, public interest and good service. the job loss Guarantee program in the above law also provides opportunities for workers who are laid off or who resign from work to get another job through a job training development program so that they can get a better and decent job. Of course, this is in accordance with the concept of justice in law, especially in protecting the Justice of the right to work and a decent livelihood and fulfilling the ius Constituendum of the mandate of Article 28D paragraph (2) of the 1945 Constitution.